2022
DOI: 10.3846/cs.2022.13320
|View full text |Cite
|
Sign up to set email alerts
|

Creativity as an Essential Aspect in Medical Education

Abstract: The article deals with the issues of developing students’ creative skills at medical educational institutions. Intensification of students’ creative potential occurs through the formation of thinking, research and communication skills, ability to interact with information means and technologies. Second-year students of General Medicine Faculty were involved in the experiment at Danylo Halytsky Lviv National Medical University in Ukraine. Experimental and control groups included 172 students in each one. We sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The second aspect that makes communication skills acquisition effective is the possibility for students to express their ideas and feelings in a relaxed environment created by them, using the techniques as rapid ideation, How Now Wow matrix and step ladder. It is worth noticing, that English teachers provide nursing students with "alternative ways of thinking-"brainstorming", analyzing personal beliefs and values and summarizing the obtained knowledge or experience about diseases, patients and the world" [13] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second aspect that makes communication skills acquisition effective is the possibility for students to express their ideas and feelings in a relaxed environment created by them, using the techniques as rapid ideation, How Now Wow matrix and step ladder. It is worth noticing, that English teachers provide nursing students with "alternative ways of thinking-"brainstorming", analyzing personal beliefs and values and summarizing the obtained knowledge or experience about diseases, patients and the world" [13] .…”
Section: Resultsmentioning
confidence: 99%
“…Aesthetic communication allows future medical caregivers to become creative and critical thinkers, which affects the students' capacity to scrutinize learning material and involves assessing information through logical reasoning and personal perspectives. Thus, the results obtained can be used in both standard and non-standard situations, as well as in developing the ability to ask original questions, find arguments, and make independent decisions" [13] . Investigations have also confirmed that some nurses may lack proficiency and assurance in their capacity to communicate distressing information.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that traditional educational processes oppress creativity is theoretically important, especially in societies in which conditions are rapidly changing. In such conditions, which have been exacerbated by the COVID-19 pandemic (Enriquez and Gargiulo, 2022), from an economic perspective, creativity has been positioned as a critical workplace competence (European Commission, 2015; Shumylo et al , 2022; OECD, 2022). I should highlight the point here that generating creative solutions is important in many professional fields, such as medicine, teaching, informatics, business, engineering and entrepreneurship (Morris and König, 2021; Davis, 2012; Ma et al , 2018; OECD, 2022).…”
Section: Introductionmentioning
confidence: 99%